IKLIM PSIKOLOGIS, USAHA KARYAWAN DAN PERFORMANSI KERJA DI PERUSAHAAN TAMBANG JAKARTA - Mulyani, Siti (Universitas Ahmad Dahlan, 2009)
This study was aimed to identify the con-elation between psychological climate and effort with performance. This hypothesis posed in this study were: 1) the correlation between psychological climate and performance; 2) the correlation between effort and performance. This subjects of this study were 29 officer in Minning Company in Jakarta. Data were collected based on two scales, that were psychological climate scale, and employee effort scale and performance was found from personnel data in organization. Based on regression analysis concluded that 1) there was no correlation between psychological climate with performance; 2) there was no con-elation between effort with performance.